Alteration of pro-carcinogenic gut microbiota is associated with clear cell renal cell carcinoma tumorigenesis - Yang, Bo-Yu; Zhao, Fang-Zhou; Li, Xuan-Hao; Zhao, Mei-Shan; Lv, Jing-Cheng; Shi, Ming-Jun; Li, Jun; Zhou, Zhi-Yuan; Wang, Jing-Jing; Song, Jian (Frontiers in Microbiology, 2023)
Objective Increasing evidence suggests that gut microbiota is involved in the occurrence and progression of urinary system diseases such as clear cell renal cell carcinoma (ccRCC). However, the mechanism of how alteration of gut metagenome promotes ccRCC remains unclear. Here we aim to elucidate the association of specific gut bacteria and their metabolites with ccRCC. Methods In a pilot case-control study among 30 ccRCC patients (RCC group) and 30 healthy controls (Control group), 16S ribosomal RNA (rRNA) gene sequencing were analyzed from fecal samples collected prior to surgery or hospitalization. Alpha diversity and beta diversity analysis of the gut microbiota were performed, and differential taxa were identified by multivariate statistics. Meanwhile, serum metabolism was measured by UHPLC-MS, and differential genes were identified based on the TCGA database. Results Alpha diversity found there were no significant microbial diversity differences of gut microbiota between the RCC group and the Control group. However, beta diversity analysis showed that the overall structures of the two groups were significantly separated (p = 0.008). Random Forests revealed the relative abundances of 20 species differed significantly between the RCC group and the Control group, among which nine species were enriched in the RCC group such as Desulfovibrionaceae, and 11 species were less abundant such as four kinds of Lactobacillus. Concomitantly, serum level of taurine, which was considered to be consumed by Desulfovibrionaceae and released by Lactobacillus, has decreased in the RCC group. In addition, macrophage-related genes such as Gabbr1 was upregulated in ccRCC patients. Conclusion Reduction of protective bacteria, proliferation of sulfide-degrading bacteria Desulfovibrionaceae, reduction of taurine, and enrichment of macrophage related genes might be the risk predictors of ccRCC.